(untitled) (Modern education and development, 2025)
This study explores the effectiveness of traditional storytelling circles in improving English pronunciation and intonation among rural learners. Recognizing storytelling as a culturally embedded and orally rich practice, the research examines how participation in regular storytelling sessions can enhance phonological awareness, rhythm, and speech patterns in English. The study highlights how this community-based, low-resource method fosters learner engagement and natural language acquisition, making it a valuable supplement to formal language instruction in under-resourced rural settings.